Composição florística das epífitas vasculares em duas fisionomias vegetais no município de Botucatu, estado de São Paulo, Brasil1 - Marcusso, Gabriel Mendes [UNESP] (2016)
We evaluated the floristic composition of vascular epiphytes, and classified them according to their ecological categories and dispersion syndrome, in a Swamp Forest (SF) and a Seasonal Semideciduous Forest (SSF), in Botucatu municipality, São Paulo. Sampling was carried monthly during one year. Comparisons with other epiphytes surveys were carried, using Jaccard Index. For species identifications, we used taxonomic literature, consult to herbarium specimens and experts. The collected specimens are deposited at the Herbário Rioclarense (HRCB). We identified 87 species, belonging to 51 genera and 13 families; the SF was the richest physiognomy. Orchidaceae, Polypodiaceae, Bromeliaceae and Piperaceae are the most representative families. Of the species sampled 2.4% are anemocoric and 87.4% are obligatory holoepiphytes. Seven species are threatened or near threatened; two of them are presumably extinct. The studied area is more similar to sites in Paraná, Rio Grande do Sul and Argentina. The present work recorded one of the major species richness in seasonal forest in the Atlantic Domain, what demonstrates the importance of floristic surveys and the protection of these small and neglected forest patches.